Application Of Demonstration Method To Improve Mathematics Learning Achievement Of Class 1 Students SD 0511 Batang Tangal Jas T.P 2020/2021 - Siti Amar Pulungan (STKIP Rokania Pasir Pangaraian, 2021)
This research is Classroom Action Research which is motivated by the low achievement of students in mathematics. The formulation of the research problem is how to apply the demonstration method to improve mathematics learning achievement for grade 1 students at SD Negeri 0511 Batang Tangal Jas for the 2020/2021 academic year. The purpose of this study was to describe the implementation of the Demonstration method strategy that could improve the mathematics learning achievement of the first graders of State Elementary School 0511 Batang Tangal Jas. The research subjects were the first grade students of the 0511 Batang Tangal Jas State Elementary School, which amounted to 20 people. The object of the research is the application of the Demonstration method and the achievement of learning mathematics. This research was conducted in two cycles. Data collection techniques used are tests, observations, and documentation. The data analysis technique in this research is descriptive analysis. Based on the results of the study, it was concluded that the application of the Demonstration method could improve the mathematics learning achievement of class I students Sekolah Dasar Negeri 0511 Batang Tangal Jas